Investigation of Stem Cell Applications on In Vitro Fertilization in Rats - GUMURDU, A; OZTURK, S; AYDEMIR, I; TUGLU, MI (Journal of the Hellenic Veterinary Medical Society, 2021)
We aimed to search the effects of bone marrow-derived mesenchymal stem cell-conditioned media on in vitro fertilization by investigation of lifetime of germ cells cleavage, degeneration rates and embryo quality. For this purpose, firstly MSCs were isolated from femurs and tibias of the rat, and cells were cultured until the fourth passage. Sperm and oocytes were collected from male and female rats. Oocytes were added in Human Tubal Fluid Media (HTFM), Single Step Media (SSM), Alpha-MEM Media (AMM) and Bone Marrow-Derived Mesenchymal Stem Cell-Conditioned Media (CM). Thousand sperm were added into the media which including oocytes. Embryos were allowed to produce by IVF. The development of the embryos was followed until the 11th day, and the arrest, degeneration rates and alive embryos were established. The embryos reached 2, 4, 8, 16 cells stages and morula stage in the CM. While AMM had a negative effect on fertilization and embryo development, the most favourable effect was shown to be caused by CM in comparison with the other medias. These results have shown that the beneficial effects of CM in IVF would be a significant increase in the rate of fertility and development of embryos.